Design and Reform of Personalized Learning Pathways for E-commerce Customer Relationship Management Courses Based on AI Technology (Journal of Global Humanities and Social Sciences, 2025)
Against the backdrop of rapid development in the e-commerce industry and the growing importance of customer relationship management, the shortcomings of traditional course instruction have become increasingly apparent. AI technology offers new opportunities for achieving personalized learning and improving teaching quality. This paper focuses on the application of AI technology in e-commerce customer relationship management courses, delving into the design and reform practices of personalized learning paths. By leveraging the advantages of AI technology, it proposes strategies for constructing personalized learning paths and discusses their application effects in teaching practice. Research indicates that personalized learning paths based on AI technology can effectively enhance students' learning interest and outcomes, providing new insights and methods for teaching reforms in e-commerce customer relationship management courses.